Beam tests for the determination of the interfacial properties of FRCM composites. (December 2022) - Cristofaro, Maria Teresa; D'Ambrisi, Angelo; Focacci, Francesco; Tanganelli, Marco; De Stefano, Mario
Abstract: Fiber Reinforced Cementitious Matrix (FRCM) materials are widely used for strengthening reinforced concrete (RC) structures. Experimental studies show that the collapse of RC elements reinforced with FRCM composites occurs due to the loss of bond of the reinforcing material. For this reason the issue of the shear stress transfer between reinforcement and concrete substrate has been extensively studied in the last years. The single-lap shear test is the most frequently adopted test configuration. In this paper the results of bond tests between a FRCM composite and concrete performed in the beam test configuration are presented. The results are used to determine the cohesive material law (CML) of the tested composite and the obtained CML is compared with that obtained on the basis of the results of single-lap shear tests. The comparison shows that the two test configurations provide similar CML.